INDEKS KEMATANGAN GONAD IKAN NILA (Oreochromis niloticus L) YANG DIBERI PAKAN ALTERNATIF DAN DIPOTONG SIRIP EKORNYA - Solang, Margaretha (Jurnal Sainstek, 2010)
This Research aim to study influence of alternative weft administration and amputation of fin tail go with the tide to maturity index of gonad (Oreochromis niloticus L). This research used of the factorial eksperiment. First factor was amputation of fin tail and second factor was alternative weft administration. Amputation of fin tail was nila fish which was not be cut tail fin, nila fish crosscut by semi from tail fin length, and nila fish crosscut by all from tail fin length (to a point last vertebrae). Alternative weft administration was small shrimp, bran admistration; small shrimp, tahu waste admistration; bran, tahu waste adminisstration; bran, tahu waste, small shrimp admistration and natural weft adminisstration . Becoming subyek in this research was 180 nila fish old age 2 months. Variable perceived at this research was maturity index of gonad fish. Quantitative data will be analysed by statistic by using Analysis of Varians (ANAVA) and when signifikan continued with Least significance Difference. Result of research demonstrated that alternative weft administration and amputation of tail fin can improve maturity index of gonad fish. Keyword: alternative weft ,amputation of tail fin, maturity index of gonad, Oreochromis niloticus.L